Significant Neutralizing Antibody and Cytolytic T Cell Responses to GEN-003, a Herpes Simplex Virus Immunotherapy, in a Phase 2b Study. (4th October 2017) - McNeil, Lisa K; Baccari, Amy; Clemens, Veronica; Dominguez, David; Fenske, Tyler; Oliphant, Thomas; Perry, James; Siddall, Nicolle; Yuan, Jin; Heineman, Thomas; Hetherington, Seth; Flechtner, Jessica B
Abstract: Background: Over 500 million people globally have genital ulcerative disease due to herpes simplex virus (HSV). Data suggest that both B- and T-cell immune responses are critical for effective control of viral replication and disease symptoms. GEN-003 is a potential immunotherapy containing two recombinant HSV-2 proteins, ICP4.2 and gD2ΔTMR combined with adjuvant, Matrix-M2™ (MM2, Novavax). In a Phase 2 clinical trial, GEN-003 resulted in a reduction in viral shedding and lesion rates. Here we report immunogenicity responses to GEN-003 through 1 year of follow up. Methods: In total, 131 adults with clinically diagnosed HSV-2 infection were randomly assigned to one of two GEN-003 dose groups (60 µg of antigens with either 50 or 75 µg MM2 adjuvant) or placebo. Subjects were immunized three times at 21-day intervals. Serum was collected on days 1, 22, 43, and 71, and at 6 and 12 months. Heparinized whole blood for peripheral blood mononuclear cell enrichment was collected on days 1, 8, and 50, and at 6 and 12 months. Humoral responses were evaluated by indirect IgG ELISA and a cell-based colorimetric HSV-2 neutralizing antibody assay. Cellular responses were evaluated by an interferon-γ (IFN-γ)/Granzyme B (GrB) fluorescent enzyme-linked immunospot assay. Results: Following the first immunization, mean IgG titers to ICP4.2 and gD2ΔTMR increased >60-fold and >8-fold from baseline, respectively, in both GEN-003 dose groups. Elevated antibody levels persisted above 8-fold through Day 71. Mean neutralizing antibody titers were >4-fold higher vs. baseline at Day 71 for both dose groups. Increases in IFN-γ, GrB, and dual-secreting T-cell responses to both vaccine antigens peaked at Day 8 post-first immunization and were sustained through Day 50 for the 60 µg GEN-003 antigens/50 µg MM2 group. T-cell responses in the 60 µg GEN-003 antigens/75 µg MM2 group peaked at Day 8 and decreased thereafter. Placebo group values did not increase from baseline for all above parameters. Further evaluation of immunogenicity at the 6 and 12-month time points will be examined. Conclusion: Overall, immunization of HSV-2 infected subjects with GEN-003 induced both cellular and humoral immune responses that may play a role in controlling both viral shedding and symptoms of genital disease. Disclosures: L. K. McNeil, Genocea Biosciences: Employee, Salary; A. Baccari, Genocea Biosciences: Employee, Salary; V. Clemens, Genocea Biosciences: Employee, Salary; D. Dominguez, Genocea Biosciences: Employee, Salary; T. Fenske, Genocea Biosciences: Employee, Salary; T. Oliphant, Genocea Biosciences: Consultant, Consulting fee; J. Perry, Genocea Biosciences: Employee, Salary; N. Siddall, Genocea Biosciences: Employee, Salary; J. Yuan, Genocea Biosciences: Employee, Salary; T. Heineman, Genocea Biosciences: Employee, Salary; S. Hetherington, Genocea Biosciences: Employee, Salary; J. B. Flechtner, Genocea Biosciences: Employee, Salary